2021
DOI: 10.1186/s12913-021-06283-w
|View full text |Cite
|
Sign up to set email alerts
|

Understanding HPV-positive women’s needs and experiences in relation to patient-provider communication issues: a qualitative study

Abstract: Background HPV testing has been integrated in cervical cancer screening program. Patient-providers relationship is extremely important to improve cervical cancer screening outcomes. This qualitative study aims to understand HPV-positive women’s needs and preferences about HCPs and patient-provider communication based on their experiences of accessing primary and specialized care. Methods We conducted 40 semi-structured interviews with HPV-positive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 48 publications
(61 reference statements)
0
10
0
Order By: Relevance
“… 29 A further reason that steered participants to engage with screening were predisposing factors such as genital warts and other health conditions (eg, infertility). 30 , 34 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 29 A further reason that steered participants to engage with screening were predisposing factors such as genital warts and other health conditions (eg, infertility). 30 , 34 …”
Section: Resultsmentioning
confidence: 99%
“… 29 , 36 , 40 Counseling was usually delivered verbally, although, in one study, women were shown videos and images and were disturbed by the description of the colposcopy procedure. 34 There was no difference in counseling whether it was conducted by qualified health personnel (eg, nurses, doctors) or trained laywomen (ie, breast health workers). 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suboptimal counseling may be attributed to deficits in clinical knowledge of modes of transmission ( Trucchi et al, 2020 ), the ability to balance time between clinical services and counseling, and providers’ bias toward women’s sexuality overall ( Leung et al, 2019 ). Literature shows that female patients appreciate knowledgeable physicians that tactfully approach HPV counseling and testing ( Qaderi et al, 2021 ), especially females with intersecting marginalized identities such as Muslim women. Educating patients about the modes of transmission and the importance of prevention through safe sex and HPV vaccines can mend some of the medical mistrust marginalized communities feel ( Ho et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%